2021
DOI: 10.4103/jips.jips_599_20
|View full text |Cite
|
Sign up to set email alerts
|

Anti candidal efficacy of commercially available triphala, neem, denture cleanser and natural aloevera leaf on heat polymerized acrylic resin

Abstract: Aim: The aim of the study was to evaluate the anticandidal efficacy of Triphala, aloe vera, Neem, and denture cleanser on heat polymerized acrylic resin. Settings and Designs: In vitro - experimental study. Materials and Methods: In this study, forty denture wearer patients were selected and were divided into four groups consisting of ten patients, namely, Group I, Group II, Group III, and Group IV, in which dentures were clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A recent study by Nair et al showed that aloe vera had the least antifungal activity when compared to the conventional denture cleansers, neem and triphala. In the current study, while comparing the mean reduction in candida count between the three groups, aloe vera was shown to be more effective than chitosan and the control group [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Nair et al showed that aloe vera had the least antifungal activity when compared to the conventional denture cleansers, neem and triphala. In the current study, while comparing the mean reduction in candida count between the three groups, aloe vera was shown to be more effective than chitosan and the control group [ 36 ].…”
Section: Discussionmentioning
confidence: 99%